The Relationship Between Parental Support on Children Oral Health and Children Dental Caries in Agroindustrial Area of Jember - Kiswaluyo; Roedy Budirahardjo; Sulistiyani; Elyda Akhya Afida Misrohmasari; Ni Luh Putu Maharani Eka Putri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Dental caries is a multifactorial disease that children experience. Parents' behavior to support children is essential in maintaining children's oral health. The social environment, such as the farming community in the agricultural environment, shapes people's behavior. This study aimed to analyze the relationship between parental support on children's oral health and dental caries in the agroindustrial area of Jember. This study is an analytical observational design with cross-sectional approach. This study was held in SDN Candijati 01 and SDN Biting 04, Arjasa Jember, and attended by 36 pairs of parents and students in 5th grade. Children were examined for the presence of dental caries based on Class 1 caries of Black Classification. A set of questionnaires was given to the parents to assess parental support on oral health. Chi-Square test was performed to find the relationship between dental caries and parental support. The study results showed that Class 1 Caries was present in 100% of children who lacked parental support on oral health. There is a significant relationship between dental caries and parental support on children's oral health in children of the agroindustrial area of Jember